Characterization of phytochemical compounds (qualitative and quantitative) in the endophytic fungi the bark of the Duwet plant - Titik Wijayanti; Anita Munawwaroh; Nuril Hidayati (Jurnal Biologi Tropis, 2022)
This study aims to characterize the phytochemical compounds in the endophytic fungi the bark of the Duwet (S. cumini L.). Duwet skin samples were taken from various regions in East Java, including Batu City, Malang Regency, Pasuruan Regency, Lamongan Regency, Gresik Regency, and Situbondo Regency. The method used in this research is an experiment, namely the isolation of endophytic fungi, qualitative and quantitative phytochemical content tests. The results showed that there were variations in the content of endophytic fungi in the duwet bark from one location to another. All samples of endophytic fungi isolate from Duwet stem bark contained flavonoid compounds, alkaloids, terpenoids, phenolics and tannins. Phytochemical compounds of endophytic fungi in the bark are the result of symbiosis between endophytic fungi and their host plants. Endophytic fungi live in intracellular tissue, then absorb nutrients from their host plants, and include phytochemical compounds found in the bark of the duwet plant.